Effects of the occupational exposure on health status among petroleum station workers, Khartoum State, Sudan - Qafisheh, Nida (Toxicol Rep, 2021)
OBJECTIVE: The hazards of petroleum station activities are greatly emphasized due to their negative impact on workers’ health and safety concerns. This study aims to assess the effect of occupational exposure among the workers in various petroleum station at the Khartoum State, Sudan. METHODS: An analytical and experimental study design is followed where 60 participants were selected through purposive sampling technique. The participants were recruited from the petroleum workstation and were considered as the lead exposed group whereas the participants who lived faraway from the petroleum station and had no exposure to lead were considered as un-exposed group. To avoid the effects of smoking on lead concentration we further divided these groups into smokers and non-smokers. IBM, SPSS was used for the statistical analysis of the collected data. RESULTS: The results show that there is no significant difference in white blood cells (WBCs) count between exposed and unexposed lead group. We also did not find significant difference in Red blood cells (RBCs) count. Participant from both groups had normal range of haemoglobin (Hb). However, haematocrit (Hct) levels were elevated in both of these groups. We also tested the platelet count in these groups and found that platelet count was slightly lower in lead exposed group as compared to the unexposed group but average count was found within the normal range. Finally, the lead concentration in serum and urine was detected of the participants. Results reveal that the serum lead concentration of non-smokers (0.58 mg/l) in the exposed group was higher than in non-smokers of unexposed group (0.49 mg/l). The lead concentration in serum of smokers in exposed group was also high (1.49 mg/l) than the lead concentration detected in serum of smokers in unexposed group (1.14 mg/l). Urine lead levels of exposed group was also high than the unexposed group in smokers and non-smokers. Mean value of lead in urine among non-smokers of the exposed and unexposed group were 0.76 mg/L and 0.19 mg/L respectively. In the case of smokers, 1.59 mg/L and 1.16 mg/L were the mean value of lead in urine for both exposed and unexposed groups respectively. CONCLUSION: From the given results it can be concluded that health safety measures for workers must be implemented to maintain good health status of workers at petroleum stations.